A Good High Place - Kimball, L. E. (Book collections on Project MUSE., 2010)
The sometimes painful adaptations of a faster-paced age are embodied, in part, in the struggles of Luella's father who, already troubled by the death of his wife, wrestles with the realization that his livelihood as a steamboat captain is becoming obsolete.